2016
DOI: 10.1088/1475-7516/2016/10/030
|View full text |Cite
|
Sign up to set email alerts
|

Consistency relations and conservation of ζ in holographic inflation

Abstract: It is well known that, in single clock inflation, the curvature perturbation ζ is constant in time on superhorizon scales. In the standard bulk description this follows quite simply from the local conservation of the energy momentum tensor in the bulk. On the other hand, in a holographic description, the constancy of the curvature perturbation must be related to the properties of the RG flow in the boundary theory. Here, we show that, in single clock holographic inflation, the time independence of correlators … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…It has been suggested, e.g., in refs. [3,[16][17][18][19][20], that these universal properties are both consequences of the invariance under the large gauge transformations. However, it was also revealed that this invariance is not sufficient to derive the consistency relation.…”
Section: Jhep10(2017)127mentioning
confidence: 96%
See 3 more Smart Citations
“…It has been suggested, e.g., in refs. [3,[16][17][18][19][20], that these universal properties are both consequences of the invariance under the large gauge transformations. However, it was also revealed that this invariance is not sufficient to derive the consistency relation.…”
Section: Jhep10(2017)127mentioning
confidence: 96%
“…In refs. [18][19][20], the analyticity in the soft limit was additionally imposed to derive the consistency relation.…”
Section: Jhep10(2017)127mentioning
confidence: 99%
See 2 more Smart Citations
“…The cosmological holographic framework however has already passed a number of non-trivial tests and we will provide additional support in this paper. Work on holographic cosmology was initiated in [9][10][11][12], with standard inflation fitting in this framework as a strongly coupled QFT (see for example [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]). Holographic cosmology also contains qualitative new models for the very Early Universe obtained by considering QFTs at weak coupling [33].…”
mentioning
confidence: 99%